Molecular Docking and In Vitro Studies of Synthesized Oxadiazole Derivatives as Urease Inhibitors - Kamran Mehdi; Obaid-ur-Rahman Abid; Saqib Khan; Is Helianti; Muhammad Ikhlas Abdjan; Aleesha Aleesha; Muhammad Ali; Naseer Ahmed (Journal of Mathematical and Fundamental Sciences)
A novel sequence of 1,3,4-oxadiazoles (7a–h) was synthesized. The compounds were characterized by IR, ¹H NMR, and MS analyses. They were also examined to determine whether they could prevent urease from functioning.  Molecular docking was done with AutoDock Vina, and the findings were visualized in Discovery Studio. The H NMR spectra showed peaks at δ 10.20 to 10.69 ppm for NH protons, δ 7.16 to 8.01 ppm for aromatic protons, and δ 4.21 to 4.37 ppm for 2H and CH₂ groups, confirming the structural details. The EI-MS spectra showed molecular ion peaks at 337 m/z with an intensity of 14-67%. Among the bioactivity-tested compounds, 7d resulted in robust activity with IC50 values of 161.6 ± 5.8 µM; compound 7e exhibited the weakest activity, at 453.6 ± 5.8 µM; and no inhibition was discovered by the 7a, 7f, and 7h compounds when compared to the Thiourea, at 21.8 ± 1.51 µM. Molecular dockings confirmed compound 7d as the best-docked complex, with a minimum energy of -7.4 kcal/mol, an RMSD value of 1.573 Å, and hydrogen interactions at His593 with the active site residue, confirming the experimental results. It was determined that 1,3,4-oxadiazoles can be employed as urease inhibitors.